One-pot syntheses of blue-luminescent 4-aryl-1H-benzo[f]isoindole-1,3(2H)-diones by T3P® activation of 3-arylpropiolic acids - Denißen, Melanie; Kraus, Alexander; Reiss, Guido J.; Müller, Thomas J. J. (Beilstein Journal of Organic Chemistry, 2017)
In situ activation of 3-arylpropiolic acids with T3P® (n-propylphosphonic acid anhydride) initiates a domino reaction furnishing 4-arylnaphtho[2,3-c]furan-1,3-diones in excellent yields. Upon employing these anhydrides as reactive intermediates blue-luminescent 4-aryl-1H-benzo[f]isoindole-1,3(2H)-diones are formed by consecutive pseudo three-component syntheses in a one-pot fashion. The Stokes shifts correlate excellently with the Hammett–Taft σR parameter indicating an extended degree of resonance stabilization in the vibrationally relaxed excited singlet state.
Keywords: absorption; cycloaddition; diversity-oriented synthesis; fluorescence; heterocycles; imidation